2016
DOI: 10.1038/srep32231
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 promotes scar fibroblasts proliferation and transdifferentiation via up-regulating MicroRNA-21

Abstract: TGF-β1, upregulated in keloid tissue, promotes the proliferation, collagen formation and differentiation of dermal fibroblasts. miR-21 is one of microRNAs first found in human genome. The aim of our study is to explore the mechanisms of miR-21 in TGF-β1-induced scar fibroblasts proliferation and transdifferentiation. In the present study, first we found that TGF-β1 promoted scar fibroblasts proliferation and transdifferentiation via up-regulating miR-21 expression, which could be attenuated when miR-21 was inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
108
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(115 citation statements)
references
References 35 publications
5
108
1
1
Order By: Relevance
“…It seems that the mechanism of the effect of this factor is through the increase of the expression of micro R 21 and through PTEN/Akt pathway. It has also been shown that this factor inhibits the pathway of NOTCH/Jagged1 and so causes scar inhibition (Jagadeesan & Bayat, ; Lichtman et al, ; Liu et al, ; Penn, Grobbelaar, & Rolfe, ). Therefore, reducing TGFβ1 can be a strategy to prevent scarring and the same has been suggested by various studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that the mechanism of the effect of this factor is through the increase of the expression of micro R 21 and through PTEN/Akt pathway. It has also been shown that this factor inhibits the pathway of NOTCH/Jagged1 and so causes scar inhibition (Jagadeesan & Bayat, ; Lichtman et al, ; Liu et al, ; Penn, Grobbelaar, & Rolfe, ). Therefore, reducing TGFβ1 can be a strategy to prevent scarring and the same has been suggested by various studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are few strategies to prevent or to treat scarring that were not so successful (Lichtman, Otero‐Vinas, & Falanga, ). Growth factors have vital roles in this process, for example, it seems that overexpression of TGFβ1 may mediate fibrosis in wound while bFGF may promote scarless healing and reduce scarring in this process(Akita, Akino, & Hirano, ; Liu et al, ; Shah, Foreman, & Ferguson, ; Shi et al, ; Song, Bian, Lai, Chen, & Zhao, ; Wang et al, ). The usage of medicinal plants to treat wound has a long history; different effective components and biological balance of their compounds are sometimes more effective and have fewer side effects in treatment of wound, one of these plants is Achillea (Akkol, Koca, Pesin, & Yilmazer, ; Ghobadian et al, ; Khosra et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [37] demonstrated that miR-21 was required for TGF-β-induced fibrogenic EMT in hepatocytes. miR-21 was overexpressed in human keloid fibroblasts induced by TGF-β1 [41]. Besides, miR-21 could promote TGF-β1-induced EMT in gastric cancer cells [42] and promotes breast cancer progression and chemoresistance through TGF-β1 stimulation [43].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Recently, miR-21 has been ascribed a crucial role in the regulation of cellular activity during physiological and pathological processes [31]. miR‑21 is widely expressed and has been found to be increased in organs and tissues which have suffered fibrogenesis or remodeling, including the heart [32], kidney [33], lung [34], asthmatic airways [35, 36], liver [37, 38], skin [39-41], and tumor tissue [42, 43]. Studies revealed that enhanced miR-21 expression is involved in the progression of lung fibrosis, and TGF-β1 plays an important role in mediating increased miR-21 expression [34, 44].…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β1 directly promotes the proliferation and differentiation of dermal fibroblasts, encouraging collagen formation via the miR-21 and PTEN/ Akt signaling pathway [17]. It can also inhibit DNA methyltransferase, thereby inducing demethylation of the promoter region of collagen genes and upregulation of collagen production [18].…”
Section: Discussionmentioning
confidence: 99%